Comparing Australian gay and bisexual men with undiagnosed and recently diagnosed HIV infection to those in the National HIV Registry - Down, I.; Prestage, G.; Brown, Graham; Ellard, J.; Guy, R.; Hellard, M.; Wilson, D.; De Wit, J.; Stoové, M.; Holt, M. (C S I R O Publishing, 2018)
© 2018 CSIRO. Background: Gay and bisexual men (GBM) with recent HIV infection are a key population to inform HIV-prevention. The National HIV Registry (NHR) provides details about all individuals diagnosed with HIV, but it is unclear how. Methods: Basic sociodemographic characteristics of GBM in the NHR who were diagnosed between 2010 and 2014 were compared with three samples of GBM: men with undiagnosed HIV infection from the Community-Based Study of Undiagnosed HIV and Testing (COUNT) study of HIV prevalence and undiagnosed infection that was conducted during 2013-14; men in the Australian Gay Community Periodic Surveys (GCPS) who were diagnosed with HIV between 2010 and 2014; and men in the HIV Seroconversion Study (SCS) who were also diagnosed in those years. Results: The NHR identified 3629 men who reported male-to-male sex as the exposure risk for their diagnosis between 2010 and 2014. COUNT identified 19 (8.9% of all men who tested HIV positive) men as having undiagnosed HIV. In the GCPS sample, 185 (2.5%) reported being diagnosed with HIV in 2010-14. In total, 367 men in the SCS received their diagnosis during 2010-14. The mean age of men in the NHR (36.8 years) was similar to that in GCPS (36.3 years) and SCS (35.1 years), while undiagnosed men in COUNT were younger (32.6 years), with no other significant differences between the samples. Conclusions: The undiagnosed men were somewhat younger than diagnosed men. To achieve earlier diagnosis of new HIV infections, improved HIV testing frequency is needed among younger men.